2020
DOI: 10.1001/jamanetworkopen.2020.12241
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Racial Disparities in Mortality Rates Among Older Adults Living in US Rural vs Urban Counties From 1968 to 2016

Abstract: Key Points Question Do historical trends exist in age-adjusted mortality rates among older adults of Black and White ancestry living in rural and urban counties in the US? Findings In this cross-sectional study of 3131 US counties over a 49-year period, racial disparities in the mortality rates of men, with the exception of men living in rural counties, decreased compared with women. Rural and urban disparities were associated with socioeconomic differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Secondly, although older adults classified as Black had generally lower mortality rates than those classified as White prior to the pandemic, these rates increased substantially during the first wave throughout the state. The initially lower rates match the finding of Ferdows et al (2020) for crude rates at the national level, and they match trends we confirmed independently using the same CDC WONDER database. The effects of higher rates of mortality at younger ages, evident both in our data and in national studies ( Woolf and Schoomaker, 2019 ), may explain these lower rates in Georgia.…”
Section: Discussionsupporting
confidence: 82%
“…Secondly, although older adults classified as Black had generally lower mortality rates than those classified as White prior to the pandemic, these rates increased substantially during the first wave throughout the state. The initially lower rates match the finding of Ferdows et al (2020) for crude rates at the national level, and they match trends we confirmed independently using the same CDC WONDER database. The effects of higher rates of mortality at younger ages, evident both in our data and in national studies ( Woolf and Schoomaker, 2019 ), may explain these lower rates in Georgia.…”
Section: Discussionsupporting
confidence: 82%
“…Some of the factors that might influence this trend is that rural counties had lower per capita income, higher unemployment rates, lower median household income, higher poverty rates, and higher proportion of adults 65 years or older. 5 Though, this report remarks the importance of early diagnosis of a patient with ATTR-CM in a southern region, rural county in the United States; these regions have showed lower proportions of cardiac amyloidosis but have a population with risk characteristics. 4 , 5 ATTR-CM is more common in men, elderly and African Americans.…”
Section: Discussionmentioning
confidence: 71%
“… 5 Though, this report remarks the importance of early diagnosis of a patient with ATTR-CM in a southern region, rural county in the United States; these regions have showed lower proportions of cardiac amyloidosis but have a population with risk characteristics. 4 , 5 ATTR-CM is more common in men, elderly and African Americans. 2 The approach to suspected cases of ATTR-CM relies on the presence of heart failure, red flag symptoms and age >65 or >70 for men and women, respectively.…”
Section: Discussionmentioning
confidence: 71%
“…These data build upon prior studies that have documented substantial county-level disparities in COVID-19 as well as a large body of literature demonstrating similar patterns in geographic disparities across the US in non-communicable diseases, such as cardiovascular disease [ 25 , 26 ]. Indeed, COVID-19 infection susceptibility and mortality has further amplified pre-existing place-based health disadvantage due to interrelated sociodemographic [ 27 ], health [ 28 ], and environmental factors [ 29 ] at the county-level and expand growing awareness of a “rural mortality penalty” [ 30 ] in the US. Recent investigations have demonstrated widening disparities in rural mortality rates due to noncommunicable diseases, such as chronic lung disease [ 31 ] and cardiovascular disease [ 32 ], compared with urban mortality rates.…”
Section: Discussionmentioning
confidence: 99%